Green transformational leadership, green entrepreneurial orientation and performance of smes: The mediating role of green product innovation - Tha'er Majali; Mahmoud Alkaraki; Muzaffar Asad; Nael Aladwan; Mazen Aledeinat (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Green practices are becoming increasingly important throughout the world. The performance of SMEs is becoming a crucial issue because of increasing awareness of consumers about environmentally friendly products; therefore, enterprises not following green practices may face a significant decline in performance. Therefore, the purpose of the study was to identify the mediating role of green product innovation between green entrepreneurial orientation, green transformational leadership, and the performance of SMEs. To meet the objectives of the study, structural equation modeling was applied to the data collected from 384 manufacturing SMEs operating in Amman, Jordan, using systematic sampling. The findings revealed that the mediating role of green product innovation was insignificant at the 5% level of significance but significant at the 10% level of significance. All other relationships were significant at the 5% level of significance. This study provides theoretical support for investing more resources in green product innovation to gain sustainability.
Keywords: 650; green entrepreneurial orientation; green product innovation; green transformational leadership; performance of SMEs